A Case of Cryptococcal Lymphadenitis in an HIV-Infected Child - Natukunda, Eva; Musiime, Victor; Ssali, Francis; Kizito, Hilda; Kityo, Cissy; Mugyenyi, Peter (AIDS research and human retroviruses, 2011)
An 8-year-old HIV-positive antiretroviral therapy-naive child developed severe headache and generalized lymphadenopathy. The serum cryptococcal antigen (CRAG) test was positive, the histology on the lymph node biopsy revealed budding yeast cells, and Cryptococcus neoformans was isolated on culture of his cerebrospinal fluid. He was treated with intravenous amphotericin B followed by oral fluconazole with a good response. Therefore cryptococcal lymphadenitis should be considered in the differential diagnosis of children presenting with lymphadenopathy and a positive serum CRAG.
Keywords: Cryptococcal; Lymphadenitis; HIV-Infected; Child